2018
DOI: 10.1515/rmeef-2017-0026
|View full text |Cite
|
Sign up to set email alerts
|

Google Trends and Structural Exchange Rate Models for Turkish Lira–US Dollar Exchange Rate

Abstract: In this paper, we use Google Trends data to proxy macro fundamentals that are related to two conventional structural determination of exchange rate models: purchasing power parity model and the monetary exchange rate determination model. We assess forecasting performance of Google Trends based models against random walk null on Turkish Lira–US Dollar exchange rate for the period of January 2004 to August 2015. We offer a three-step methodology for query selection for macro fundamentals in Turkey and the US. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Accordingly, Bulut (2018) suggests using Google Trends data to nowcast the future exchange rate movement. Bulut and Dogan (2018) used Google Trends data for the forecasting of the USD-Turkish Lira exchange rate using two structural models (purchasing power parity and a monetary model) and found that these out-of-sample forecasts performed better compared with a random walk model.…”
Section: Uncertainty and Its Measuresmentioning
confidence: 99%
“…Accordingly, Bulut (2018) suggests using Google Trends data to nowcast the future exchange rate movement. Bulut and Dogan (2018) used Google Trends data for the forecasting of the USD-Turkish Lira exchange rate using two structural models (purchasing power parity and a monetary model) and found that these out-of-sample forecasts performed better compared with a random walk model.…”
Section: Uncertainty and Its Measuresmentioning
confidence: 99%
“…Accordingly, Bulut (2018) suggests using Google Trends data to nowcast the future exchange rate movement. Bulut and Dogan (2018) used Google Trends data for the forecasting of the USD-Turkish Lira exchange rate using two structural models (purchasing power parity and a monetary model) and found that these out-of-sample forecasts performed better compared with a random walk model.…”
Section: Uncertainty and Its Measuresmentioning
confidence: 99%